A prison called school : creating effective schools for all learners - Metzger, Maure Ann, 1957- (Lanham, Maryland : Rowman & Littlefield, 2015)
Why are our educational institutions and practices such a poor fit for so many students? A Prison Called School addresses the complex issues that place many students at a disadvantage as they try to survive yet another hurdle in life-school. Although some students are able to navigate and succeed in the current system, other students struggle to survive a system that is unable to meet their needs. For those students, school can feel like a twelve-year prison sentence. Students who cannot fit the outdated, one-size-fits-all model, are further penalized by a system that blames the struggling student rather than holding the institution accountable. For students to thrive in school, the system, not the students, must change in deep and substantial ways. A Prison Called School is a powerful catalyst for creating the empowering, engaging, and effective learning environments that all students need to succeed in school and life.
Life on the inside -- From idealism to institutionalism -- The prisoners -- Disempowered to disengaged -- New form, not reform -- Valuing our youth, valuing our future -- The power of empowerment -- Real learning for real life -- Engaged for learning -- Partnerships that transform.
Includes bibliographical references (pages 197-208) and index.
Keywords: School improvement programs; Educational change; Educational planning; Effective teaching